Characterization and metabolomic profiling of endophytic bacteria isolated from Moringa oleifera and Piper betel leaves - V. R. Chavda; S. B. Bhatt; V. R. Umaretiya; H. P. Gajera; S. M. Padhiyar; U. K. Kandoliya; M. V. Parakhia (Scientific Reports)
Abstract Endophytes are microorganisms residing in plant tissues without causing harm and their relevance in medicinal plants has grown due to their biomolecules used in pharmaceuticals. This study isolated two endophytic bacterial strains from the leaves of M. oleifera and P. betel collected from Junagadh Agricultural University. The isolates were characterized morphologically and physio-biochemically, confirming them as gram-positive or gram-negative rods and cocci. Identification using 16S rRNA gene sequencing identified isolates belonging to various genera, including Priestia aryabhattai and Kocuria rhizophila The SEM characterization of the five selected isolates revealed diverse morphological structures, including coccus and rod shapes, organized in various formations. Isolates varied in size, with N3 (Kocuria rhizophila) cocci and S5 (Priestia aryabhattai) rods. Metabolomic analysis using GC/MS and LC–MS revealed diverse metabolic profiles with key compounds like n-Hexadecanoic acid, Pyrrolo[1,2-a]pyrazine-1,4-dione, Dihydrocapsaicin, and β-Homoproline, highlighting the potential of these endophytic bacteria in agricultural applications due to their roles in membrane integrity, antioxidant properties, stress response, and antibacterial activity.